The Effect of KWL Strategy on EFL Students’ Reading Comprehension Achievement - Zuriah, Siti; Mutia, Utin (EEdJ: English Education Journal, 2023)
This study sought to ascertain whether implementing KWL (Know, Want, Learned) has a significant effect on EFL students' success with reading comprehension of a public junior high school in Pangkalpinang, Bangka Belitung province. This research employed experimental research with quasi-experimental design. The sample of this study was the eight-graders. The sample consisted of 80 students’ which belongs to two classes; 42 experimental class and 38 students’ in control class. The test was analyzed by using t-test analysis of SPSS 22 (Statistical Package for the Social Sciences). The result of study showed it was effective to use KWL strategy by obtaining this result: the experimental class mean score was 79.45, which means it was higher than the control class’ (mean=79.37). In conclusion, KWL strategy use significantly influences how well students understand what they read.